(untitled) (New York, 2006)
The Leenders’ text provides a comprehensive introduction to the purchasing and supply chain management field, supported by 50 case studies. Cases cover purchasing and supply chain issues in a variety of settings, from process industries to high tech manufacturing and services as well as public institutions. Supply Management concepts, both strategic and tactical, have been expanded throughout the text, particularly in new chapters on Supply Law and Ethics, Public Supply, and Supplier Relations. While all basic tenets of the purchasing function and cost issues remain, the coverage of the field is state of the art highlighting the supply chain approach.
Keywords: Industrial procurement.,Materials management.,Quản trị vật liệu